On Waring's problem for a prime modulus - Dubickas, A. (Nonlinear Analysis: Modelling and Control, 1999)
We obtain a lower bound for the minimum over positive integers such that the sum of certain powers of some integers is divisible by a prime number, but none of these integers is divisible by this prime number.
Keywords: Waring's problem modulo prime number